UDC 621.565.93/95 INFLUENCE OF SURFACE LAYER THICKNESS ON HYDRAULIC RESISTANCE OF THE DEVICE : Purpose of the work: The increase in the thickness of the scale on the inner surfaces of technological pipes reduces the cross-sectional area of the pipe, thereby decreasing its conductivity. As a result, the coefficient of friction in the pipe increases, which in turn leads to an increase in its hydraulic resistance. This causes a sharp increase in the amount of energy consumed, as the required pump power for fluid transportation rises accordingly - Ismailov, Mirzaakbar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The results obtained show that increasing the thickness of the outer layer on the surface of the heat exchange pipe, in addition to reducing its heat transfer characteristics, also leads to a sharp increase in the hydraulic resistance in the pipe. This increases energy consumption and negatively affects the operation of the device at full capacity.